ANALISIS PENGENDALIAN KAS DALAM MENUNJANG LIKUDITAS KOPERASI TELKOMSEL WILAYAH VIII SULMALIRJA - Arifani Arifani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
cash control within the company do to support liquidity. Revenue fund, the fund up to a systematic approach and the internal management of cash flow (flow of funds), became an inseparable part of the finance function. In the context of cash management, no solvent term describes a situation where the company does not have the necessary liquidity to pay obligations.